Da vida-memórias de minha mãe : contranarrativas autodefinidas de trabalhadoras domésticas racializadas do Dona Sinhaninha, Oliveira-MG. - Rafaela Rodrigues de Paula (2024)
This dissertation is the result of biographical ethnographic research with three racialized domestic workers, Luzia, Sol and Lourdes, who carry out such work in the Dona Sinhaninha neighborhood, in the city of Oliveira, in Minas Gerais. Aiming to analyze their trajectories, it presents how the processes of self-definitions (Collins, 2019c), outlined by the workers, make it possible to manage the images of control (Collins, 2019b) that permeate them. Understanding images of control as colonial images of enslaved black women that have been imprisoned over time in the collective imagination, triggering expectations in relation to the bodies and work of black women. This research is specifically dedicated to bringing together the American image of the mammy (Collins, 2019b) and the Brazilian image of the black mother (Gonzalez, 2020j), which are used as a way of justifying the intersectional oppressions that permeate the trajectories of domestic workers , seeking to control the meanings of their bodies and work. The process of self-definition is understood as a possible response given by black women, who, through their experiences, elaborate other meanings about their work and lives. With all this in mind, interviews were carried out with the three women, between the years 2022-2023 in the city of Oliveira. As the researcher is the daughter of one of the interlocutors, Luzia, the research also discusses positionalities, memories and intimacy based on the challenges and implications of an ethnography at home, with a mother-interlocutor and an anthropologist-daughter. The three workers present three diverse and plural scenarios about the realities of domestic work in Brazil, in which the image of control, meanings and expectations are present, whether in the narratives of the relationships established within the homes in which they work, encompassing relationships of (almost) kinship, long-term labor relations, and also the reality of domestic work in a context of inheritance, in which the job passes from mother to daughter. As part of the self-definition process, they demonstrate perceptions about the realities of work, of themselves, and in the construction of their trajectories in other spaces beyond domestic work. I argue then that the narratives elaborated by these women about themselves, based on their experiences and trajectories inside and outside domestic work, constitute self-defining counter-narratives about themselves and work, which go against the colonial narratives of the images of control over the domestic work carried out by them.